1999
DOI: 10.1017/s0954579499001947
|View full text |Cite
|
Sign up to set email alerts
|

Theory of mind and emotion-recognition functioning in autistic spectrum disorders and in psychiatric control and normal children

Abstract: The hypothesis was tested that weak theory of mind (ToM) and/or emotion recognition (ER) abilities are specific to subjects with autism. Differences in ToM and ER performance were examined between autistic (n = 20), pervasive developmental disorder—not otherwise specified (PDD-NOS) (n = 20), psychiatric control (n = 20), and normal children (n = 20). The clinical groups were matched person-to-person on age and verbal IQ. We used tasks for the matching and the context recognition of emotional expressions, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
117
3
17

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(151 citation statements)
references
References 7 publications
14
117
3
17
Order By: Relevance
“…In this perspective, scalar implicatures concern the attribution of first-order mental states, as they involve recognizing the speaker's informative intention. This may explain why participants with ASD did so well on the scalar implicature tasks, since several studies investigating theory of mind task in persons with ASD of average or above average intelligence have shown that a considerable number of such individuals-and those with Asperger syndrome in particular-can pass first-order and even second-order theory of mind tasks (Bauminger and Kasari 1999;Bowler 1992;Buitelaar et al 1999;Dahlgren and Trillingsgaard 1996;Happé 1994;Ozonoff et al 1991;Tager-Flusberg and Sullivan 1994). Finally, it is possible that the experimental setting may have facilitated task performance, since communicative demands are reduced in a computerized task (Ozonoff 1995).…”
Section: Discussionmentioning
confidence: 99%
“…In this perspective, scalar implicatures concern the attribution of first-order mental states, as they involve recognizing the speaker's informative intention. This may explain why participants with ASD did so well on the scalar implicature tasks, since several studies investigating theory of mind task in persons with ASD of average or above average intelligence have shown that a considerable number of such individuals-and those with Asperger syndrome in particular-can pass first-order and even second-order theory of mind tasks (Bauminger and Kasari 1999;Bowler 1992;Buitelaar et al 1999;Dahlgren and Trillingsgaard 1996;Happé 1994;Ozonoff et al 1991;Tager-Flusberg and Sullivan 1994). Finally, it is possible that the experimental setting may have facilitated task performance, since communicative demands are reduced in a computerized task (Ozonoff 1995).…”
Section: Discussionmentioning
confidence: 99%
“…This potential overlap is supported by findings of the presence of symptoms of PDD in children with ADHD, and vice versa. The PDD symptoms that are reported to occur most frequently and in a majority of children with ADHD are impairments in social interaction, especially the inability to conceive other individuals' feelings and thoughts (Buitelaar et al 1999, Clark et al 1999, Santosh and Mijovic 2004. Symptoms of communication problems, and stereotyped and repetitive behaviors, have been reported to occur frequently as well in children with ADHD (Clark et al 1999, Santosh andMijovic 2004).…”
Section: Introductionmentioning
confidence: 99%
“…These studies add to two other findings indicating that PDD and ADHD originate from similar underlying deficits. First, apart from symptom overlap, overlap in Theory of Mind and executive function deficits between the two disorders has been identified (Buitelaar et al 1999, Geurts et al 2004, Happé et al 2006, Jonsdottir et al 2006, Nyden et al 1999, Ozonoff and Jensen 1999, Yuill and Lyon 2007. This may point to a shared underlying endophenotype between ADHD and PDD.…”
Section: Introductionmentioning
confidence: 99%
“…In clinical practice it is important to focus on functional analysis of the co-morbid behaviors, before starting to treat the comorbid conditions as such. On the other hand there is an overlap: children with ADHD may perform less well on Theory of Mind tests 56 and social anxiety may be difficult to discern from a lack of reciprocity as seen in PDD. Sometimes, the definitive diagnose has to be postponed until older ages.…”
Section: Differential Diagnosismentioning
confidence: 99%